Preparation method of porous sodium fluoride adsorbent particles

Through proportional mixing and process optimization, porous sodium fluoride adsorbent particles with high specific surface area and high purity were prepared, which solved the problem of insufficient adsorbent performance in the prior art, and achieved more efficient hydrogen fluoride adsorption and longer Service life.

CN119236869APending Publication Date: 2025-01-03THE 404 COMPANY LIMITED CHINA NAT NUCLEAR
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411081235.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The prior art is difficult to prepare porous sodium fluoride adsorbent particles with a large specific surface area, a longer service life and are not prone to powder loss, which cannot meet the strict requirements for adsorption of hydrogen fluoride impurities in the fluorine gas supply system.

Method used

By mixing raw materials such as sodium fluoride powder, distilled water, sodium carboxymethylcellulose, 40% hydrofluoric acid solution and anhydrous sodium carbonate, drying, ball milling, screening, tableting and sintering, the high-quality preparation is prepared by mixing raw materials such as sodium fluoride powder, distilled water, sodium carboxymethylcellulose, 40% hydrofluoric acid solution and anhydrous sodium carbonate. Porous sodium fluoride adsorbent granules with specific surface area and high purity.

Benefits of technology

It significantly improves the absorption effect of hydrogen fluoride exhaust gas and fluoride purification, extends the service life of the adsorbent, and avoids powder loss. It is suitable for harsh fluoride gas environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236869A_ABST
    Figure CN119236869A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of porous sodium fluoride adsorbent particles. The method comprises the following steps: 1, mixing raw materials; 2, drying, ball milling and screening; step 3, tabletting; step 4, sintering; the specific surface area of the porous sodium fluoride adsorbent particles can reach 2.4 m < 2 > / g and is obviously increased compared with the specific surface area of 0.2-0.5 m < 2 > / g of traditional sodium fluoride adsorbent particles, and the sodium fluoride adsorbent particles are high in purity, high in reusability, not prone to powder falling and more suitable for being used in the environment with strict requirements for adsorbents.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This patent relates to the technical field of adsorbent preparation, and specifically to a method for preparing porous sodium fluoride adsorbent particles. Background Art

[0002] Fluorine-containing waste gas is a type of waste gas that is more likely to appear in industrial production. In order to reduce the pollution of waste gas to the environment and the harm to personnel, factories need to treat the waste gas. The treatment methods of fluorine-containing gas can be divided into combustion method, adsorption method, catalytic decomposition method, electric scrubbing method and plasma decomposition method. At present, the adsorption method is often used in industry to separate and purify substances. The adsorption method for separating gases is to use the difference in the adsorption characteristics of gases on solid materials and the characteristics that the adsorption amount changes with the pressure and temperature to achieve gas separation or purification.

[0003] Sodium fluoride is the most commonly used adsorbent material in industry. In the fluorine gas supply system, sodium fluoride traps can be used to remove hydrogen fluoride impurities entrained in fluorine gas at a lower temperature. The adsorption is chemical adsorption, and the reaction is reversible. Desorption occurs when the temperature rises to generate hydrogen fluoride and sodium fluoride, which can effectively realize the repeated reuse of the adsorbent. At present, the base materials for preparing sodium fluoride adsorbents are mainly sodium fluoride and sodium hydrogen fluoride. The molding process mostly uses the base material and water to mix and then directly press into granules, and then sinter at a certain temperature. There are also reports on the preparation of sodium fluoride adsorbents using colloidal chemical synthesis. However, there are few studies on the preparation of porous sodium fluoride adsorbent particles with a large specific surface area, a longer service life and not easy to fall off. Therefore, it has become an urgent problem to study and prepare porous sodium fluoride adsorbent particles that meet the use requirements and improve their key technical indicators. Summary of the invention

[0004] The purpose of the present invention is to provide a porous sodium fluoride adsorbent particle, which has a larger specific surface area than traditional sodium fluoride adsorbent particles, and has higher purity, longer service life, is not prone to powder loss, and is more suitable for use in an environment with strict requirements for hydrogen fluoride impurity adsorption in a fluorine gas supply system.

[0005] A process route for preparing porous sodium fluoride adsorbent particles is provided. The process route fully considers a series of key variables such as raw material type, raw material ratio, mixing method, sintering parameters, pressing parameters, etc., and obtains the best process parameter combination for preparing adsorbent particles through experiments, thereby further improving the absorption effect of hydrogen fluoride tail gas and the use effect of sodium fluoride adsorbent in processes such as fluoride purification.

[0006] The technical solution of the present invention is as follows: A method for preparing porous sodium fluoride adsorbent particles comprises the following steps;

[0007] Step 1: Mix the raw materials in proportion;

[0008] Step 1.1: prepare a main material mixture, weigh sodium fluoride powder, distilled water, and sodium carboxymethyl cellulose powder as a binder and a pore-forming agent, and mix them evenly to obtain a main material mixture;

[0009] Step 1.2: Prepare an auxiliary material mixture; prepare 40% hydrofluoric acid solution and anhydrous sodium carbonate powder, add distilled water in advance, and cool the distilled water; pour the anhydrous sodium carbonate powder into it and fully dissolve it; when the water temperature is below 10°C, pour 40% hydrofluoric acid into it, and after the reaction is fully completed, obtain an auxiliary material mixture;

[0010] Step 1.3: preparing an adsorbent mixed material, mixing the prepared auxiliary material mixture with the main material mixture to obtain a colloidal adsorbent mixed material;

[0011] Step 2: drying, ball milling and screening;

[0012] The mixed material obtained in step 1 is dried in the shade, and the mixture and grinding beads are placed in a ball mill for ball milling. After the ball milling is completed, the mixture is placed in a vibrating sieve machine for sieving.

[0013] Step 3: tableting;

[0014] Adding the adsorbent mixture prepared in step 2 into a tablet press to prepare adsorbent particles;

[0015] Step 4: sintering;

[0016] The adsorbent particles prepared in step three are sintered.

[0017] In the steps 1.1 and 1.2, a plexiglass rod is used for thorough stirring.

[0018] In the step 1.1, 60 parts of sodium fluoride powder, 35 parts of distilled water, and 5 parts of sodium carboxymethyl cellulose powder are weighed as a binder and a pore-forming agent by mass fraction; in the step 1.2, 40 parts of 40% hydrofluoric acid solution and 40 parts of anhydrous sodium carbonate powder are prepared by mass fraction, and 20 parts of distilled water are added in advance.

[0019] In the step 1.3, after mixing evenly, let it stand for 30 minutes, and skim off the upper clear liquid in the bucket.

[0020] In the step 2, the grinding beads are made of ceramic material, the mass ratio of the grinding beads to the mixture is 5:1, the diameter of the grinding beads is 4-6 mm, the ball milling speed is controlled to be 400 rpm, the ball milling time is 0.5-1.5 h, and after the ball milling is completed, the mixture is placed in a 1-mesh vibrating screen for screening.

[0021] In the step 2, the moisture content of the powder is reduced to 10%.

[0022] In the step 4, the adsorbent particles prepared in the step 3 are placed in a box-type resistance furnace for high-temperature sintering. The specific heating steps are as follows:

[0023] First, the temperature was raised from room temperature to 250°C and kept for 60 minutes;

[0024] Secondly, heat to 500℃ and keep warm for 30min;

[0025] Then the product is cooled in the furnace to obtain the finished product of the additive granules.

[0026] In the step 1, the auxiliary material mixture is prepared by adding sodium bifluoride aqueous solution to distilled water.

[0027] In the step 1.3, the mass ratio of the main material mixture to the auxiliary material mixture is 1:1.

[0028] The remarkable effect of the present invention is that the specific surface area of ​​the porous sodium fluoride adsorbent particles in the present invention can reach 2.4m 2 / g, compared with the specific surface area of ​​traditional sodium fluoride adsorbent particles of 0.2-0.5m 2 / g has been significantly improved, and the sodium fluoride adsorbent particles in the present invention have high purity, strong reusability, and are not prone to powdering, making them more suitable for use in environments with strict requirements on adsorbents. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Attached Figure 1 A schematic diagram of the complete process flow for preparing the adsorbent of the present invention; DETAILED DESCRIPTION

[0030] Many specific details are described in the following description to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways than those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present application, so the present application is not limited by the specific implementation disclosed below.

[0031] The terms used in one or more embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit one or more embodiments of the present application. The singular forms of "a", "said" and "the" used in one or more embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used in one or more embodiments of the present application refers to and includes any or all possible combinations of one or more associated listed items.

[0032] It should be understood that, although the terms first, second, etc. may be used to describe various information in one or more embodiments of the present application, such information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of one or more embodiments of the present application, the first may also be referred to as the second, and similarly, the second may also be referred to as the first.

[0033] A method for preparing porous sodium fluoride adsorbent particles is characterized in that the porous sodium fluoride particles are prepared by using sodium fluoride raw materials and auxiliary materials such as sodium bifluoride, hydrofluoric acid, anhydrous sodium carbonate, sodium carboxymethyl cellulose, etc. through processes such as proportioning and mixing, drying, ball grinding, screening, tableting, sintering, etc., and detecting key technical indicators thereof.

[0034] Step 1: Mix the raw materials

[0035] (1) Preparation of main material mixture

[0036] 60 parts of sodium fluoride powder (analytical grade), 35 parts of distilled water, and 5 parts of sodium carboxymethyl cellulose powder were weighed as a binder and a pore-forming agent according to mass fraction, added into a plastic stirring barrel in sequence, stirred fully with a plexiglass rod, and mixed evenly to obtain a material mixture.

[0037] (2) Preparation of auxiliary material mixture

[0038] Prepare 40 parts of 40% hydrofluoric acid solution (analytical pure) and 40 parts of anhydrous sodium carbonate powder (analytical pure) by mass, add 20 parts of distilled water in a plastic mixing barrel in advance, and cool the distilled water by using a cold water bath outside the barrel. Pour the anhydrous sodium carbonate powder into the barrel at one time, and stir it with a plexiglass rod to fully dissolve it. When the water temperature is below 10°C, slowly pour 40% hydrofluoric acid into the mixing barrel along the barrel wall, and use a plexiglass rod to stir continuously during the process to keep the acid-base neutralization reaction within controllable limits. After the reaction is fully completed, the auxiliary material mixture is obtained. Due to the excess acid, the main components of the mixture are sodium fluoride, sodium bifluoride, carbon dioxide gas and excess hydrofluoric acid generated by the reaction, which ensures that the reaction will not introduce non-volatile impurities and effectively forms more pores in the generated powder particles.

[0039] (3) Preparation of adsorbent mixed material

[0040] Add the auxiliary material mixture prepared in step 1 into the plastic mixing barrel containing the main material mixture, mix well and let stand for 30 minutes, skim off the upper clear liquid in the barrel to prepare a colloidal adsorbent mixed material.

[0041] Step 2: Drying, ball milling and screening

[0042] The mixed material obtained in step 1 is spread out in a well-ventilated environment to dry naturally in the shade, so that the moisture of the powder is reduced to 10%. The mixture and the grinding beads are placed in a ball mill for ball milling. The grinding beads are made of ceramic materials. The mass ratio of the grinding beads to the mixture is 5:1. The diameter of the grinding beads is 4-6mm. The ball milling speed is controlled to be 400rpm and the ball milling time is 0.5-1.5h. After the ball milling is completed, the mixture is placed in a 1-mesh vibrating screen for screening.

[0043] Step 3: Tablet pressing

[0044] The adsorbent mixture prepared in step 2 is added to a rotary tablet press to prepare adsorbent particles. The pressing cylinder punch pressure is adjusted to a range of 35-60N to obtain particles with high structural strength. The size of the adsorbent obtained is a cylindrical particle with a diameter of 10 mm.

[0045] Step 4: Sintering

[0046] The adsorbent particles prepared in step 3 are placed in a box-type resistance furnace for high-temperature sintering to remove impurities and form internal loose pores. The specific heating steps are as follows:

[0047] First, the temperature was raised from room temperature to 250°C and kept for 60 minutes;

[0048] Secondly, heat to 500℃ and keep warm for 30min;

[0049] Then the product is cooled in the furnace to obtain the finished product of the additive granules.

[0050] During the heating process, attention should be paid to air circulation to remove hydrogen fluoride from the adsorbent particles and promote the complete decomposition of impurities and the complete evaporation of water.

[0051] The sodium fluoride particles prepared by the above method were tested for relevant technical indicators. The main component was sodium fluoride, and the impurity content of sodium carbonate was less than 10. -3 , with a specific surface area of ​​0.6m 2 / g or above, the fragmentation pressure is 80-120N, and the selective adsorption effect on the specified fluorine-containing gas is good.

[0052] In the method for preparing the adsorbent described in the technical solution, the specific steps and conditions can be selected with reference to conventional operations in the art.

[0053] In the preparation method of the adsorbent described in the technical solution, under simple conditions, the auxiliary material mixture can be replaced by an aqueous solution of sodium bifluoride. More generally, the auxiliary material mixture can be prepared by adding commercially available sodium bifluoride powder (analytical grade) to distilled water, with a mass fraction of 60 parts:40 parts being preferred.

[0054] In the preparation method of the adsorbent described in the technical scheme, the mass ratio of the main material mixture to the auxiliary material mixture is not particularly limited, that is, the main material mixture or the auxiliary material mixture can be used alone for the drying and ball milling described in step 2, or the main material mixture and the auxiliary material mixture can be used in a proportion according to actual conditions, and the preferred ratio is 1:1.

[0055] In the preparation method of the adsorbent described in the technical solution, there is no special requirement for the adsorbent particle size, which can be selected according to the size of the tablet press core plate. The thickness of the adsorbent particles is generally preferably 4-8 mm.

[0056] The sintering conditions described in the technical solution can be conventional sintering conditions in the art, and the sintering temperature is preferably 200-800°C, more preferably 200-600°C, and further preferably 250-400°C; when the sintering temperature is low, the specific surface area of ​​the product increases, but the structural strength decreases.

[0057] Without violating the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0058] The reagents and raw materials used in the present invention are commercially available.

[0059] Several specific embodiments are given below

[0060] Embodiment 1:

[0061] according to Figure 1 The process flow shown is as follows: weigh 12kg of sodium fluoride powder (analytical grade), 7kg of distilled water, and 1kg of sodium carboxymethyl cellulose powder, add them to a plastic mixing barrel in sequence, and stir them for 10 minutes using a plexiglass rod to obtain a sodium fluoride solution. Prepare 8kg of 40% hydrofluoric acid solution (analytical grade) and 8kg of anhydrous sodium carbonate powder (analytical grade), pre-add 4kg of distilled water to a plastic mixing barrel, and cool the distilled water using a cold water bath outside the barrel. Pour the anhydrous sodium carbonate powder into the barrel at one time and stir it with a plexiglass rod to fully dissolve it. When the water temperature is below 10°C, slowly pour 40% hydrofluoric acid into the mixing barrel along the barrel wall, and use a plexiglass rod to stir continuously during the process to keep the acid-base neutralization reaction within controllable limits. After the reaction is fully completed, pour the mixture into the sodium fluoride solution barrel and stir it thoroughly to obtain a sodium fluoride adsorbent mixed material. After mixing evenly, let it stand for 30 minutes, skim off the upper clear liquid in the barrel, and prepare a colloidal adsorbent mixed material.

[0062] The obtained mixed material was spread out in a well-ventilated environment and dried naturally in the shade for 2 days to reduce the moisture of the powder to about 10%. The mixture and ceramic grinding beads were placed in a ball mill for ball milling. The diameter of the grinding beads was 4 mm, the ball milling speed was controlled to be 400 rpm, and the ball milling time was 1 hour. After the ball milling was completed, the mixture was placed in a 1-mesh vibrating screen for sieving.

[0063] The adsorbent mixture after screening is added to a rotary tablet press to prepare adsorbent particles. The pressing cylinder punch top pressure is 50N, and the tablet press core disk rotates at a constant speed of 5rpm, and 60 particles can be produced per minute. The size of the obtained adsorbent is a cylindrical particle with a diameter of 10×6mm.

[0064] The pressed adsorbent particles are placed in a box-type resistance furnace for high-temperature sintering. The specific heating steps are as follows:

[0065] First, the temperature was raised from room temperature to 250°C at a rate of 5°C per minute and kept at this temperature for 60 minutes;

[0066] Secondly, the temperature was raised to 500°C at a rate of 2°C per minute and kept at this temperature for 30 minutes;

[0067] Then the product is cooled in the furnace to obtain the finished product of the additive granules.

[0068] The key technical indicators of the porous sodium fluoride adsorbent prepared in Example 1 were measured using scanning electron microscopy, surface area analyzer, X-ray diffractometer, hardness tester and other means. The average specific surface area was 1.50 m 2 / g, average fracture pressure 102N, XRD analysis shows that its composition is single sodium fluoride, and the proportion of sodium carbonate impurity is less than 10 -3 .

[0069] In order to compare the performance indicators of adsorbent particles pressed from different main and auxiliary materials, Examples 2 and 3 were designed.

[0070] Embodiment 2:

[0071] Weigh 24 kg of sodium fluoride powder (analytical grade), 14 kg of distilled water, and 2 kg of sodium carboxymethyl cellulose powder, add them into a plastic stirring barrel in sequence, and stir for 10 minutes using a plexiglass rod to prepare a sodium fluoride solution. Let it stand for 30 minutes, skim off the upper clear liquid in the barrel, and prepare an adsorbent mixed material. The subsequent process remains the same as in Example 1.

[0072] The key technical indicators of the porous sodium fluoride adsorbent prepared in Example 2 were measured using scanning electron microscope, surface area analyzer, X-ray diffractometer, hardness tester and other means. The average specific surface area was 0.83 m 2 / g, average fracture pressure 112N, XRD analysis shows that its composition is a single sodium fluoride substance, and the sodium carbonate impurity content is less than 10 -3 .

[0073] Embodiment 3:

[0074] Weigh 12 kg of sodium fluoride powder (analytical grade), 7 kg of distilled water, and 1 kg of sodium carboxymethyl cellulose powder, add them into a plastic stirring bucket in sequence, and stir with a plexiglass rod for 10 minutes to prepare a sodium fluoride solution.

[0075] 12 kg of sodium bifluoride powder (analytical grade) was weighed and added to the sodium fluoride solution, stirred thoroughly and allowed to stand for 30 minutes, and the upper clear liquid in the bucket was skimmed off to prepare an adsorbent mixed material. The subsequent process was the same as in Example 1.

[0076] The key technical indicators of the porous sodium fluoride adsorbent prepared in Example 3 were measured using scanning electron microscope, surface area analyzer, X-ray diffractometer, hardness tester and other means. The average specific surface area was 2.32 m 2 / g, with an average fracture pressure of 82N. XRD analysis showed that its composition was a single sodium fluoride substance, and the proportion of sodium carbonate impurities was less than 10 -3 .

[0077] The above description is only a preferred embodiment of this patent and is not intended to limit this patent. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of this patent should be included in the scope of protection of this patent.

[0078] It should be noted that, for the above-mentioned method embodiments, for the sake of simplicity of description, they are all expressed as a series of action combinations, but those skilled in the art should be aware that the present application is not limited by the described action sequence, because according to the present application, certain steps can be performed in other sequences or simultaneously. Secondly, those skilled in the art should also be aware that the embodiments described in the specification are all preferred embodiments, and the actions and modules involved are not necessarily required by the present application.

[0079] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0080] The preferred embodiments of the present application disclosed above are only used to help explain the present application. The optional embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of the present application. The present application selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present application, so that those skilled in the art can understand and use the present application well.

Claims

1. A method for preparing porous sodium fluoride adsorbent particles, characterized in that: The steps include: Step 1: Mix the raw materials in proportion; Step 1.1: prepare a main material mixture, weigh sodium fluoride powder, distilled water, and sodium carboxymethyl cellulose powder as a binder and a pore-forming agent, and mix them evenly to obtain a main material mixture; Step 1.2: Prepare an auxiliary material mixture; prepare 40% hydrofluoric acid solution and anhydrous sodium carbonate powder, add distilled water in advance, and cool the distilled water; pour the anhydrous sodium carbonate powder into it and fully dissolve it; when the water temperature is below 10°C, pour 40% hydrofluoric acid into it, and after the reaction is fully completed, obtain an auxiliary material mixture; Step 1.3: preparing an adsorbent mixed material, mixing the prepared auxiliary material mixture with the main material mixture to obtain a colloidal adsorbent mixed material; Step 2: drying, ball milling and screening; The mixed material obtained in step 1 is dried in the shade, and the mixture and grinding beads are placed in a ball mill for ball milling. After the ball milling is completed, the mixture is placed in a vibrating sieve machine for sieving. Step 3: tableting; Adding the adsorbent mixture prepared in step 2 into a tablet press to prepare adsorbent particles; Step 4: sintering; The adsorbent particles prepared in step three are sintered.

2. The method for preparing porous sodium fluoride adsorbent particles according to claim 1, characterized in that: In the steps 1.1 and 1.2, a plexiglass rod is used for thorough stirring.

3. The method for preparing porous sodium fluoride adsorbent particles according to claim 1, characterized in that: In the step 1.1, 60 parts of sodium fluoride powder, 35 parts of distilled water, and 5 parts of sodium carboxymethyl cellulose powder are weighed as a binder and a pore-forming agent by mass fraction; in the step 1.2, 40 parts of 40% hydrofluoric acid solution and 40 parts of anhydrous sodium carbonate powder are prepared by mass fraction, and 20 parts of distilled water are added in advance.

4. The method for preparing porous sodium fluoride adsorbent particles according to claim 3, characterized in that: In the step 1.3, after mixing evenly, let it stand for 30 minutes, and skim off the upper clear liquid in the bucket.

5. The method for preparing porous sodium fluoride adsorbent particles according to claim 1, characterized in that: In the step 2, the grinding beads are made of ceramic material, the mass ratio of the grinding beads to the mixture is 5:1, the diameter of the grinding beads is 4-6 mm, the ball milling speed is controlled to be 400 rpm, the ball milling time is 0.5-1.5 h, and after the ball milling is completed, the mixture is placed in a 1-mesh vibrating screen for screening.

6. The method for preparing porous sodium fluoride adsorbent particles according to claim 1, characterized in that: In the step 2, the moisture content of the powder is reduced to 10%.

7. The method for preparing porous sodium fluoride adsorbent particles according to claim 1, characterized in that: In the step 4, the adsorbent particles prepared in the step 3 are placed in a box-type resistance furnace for high-temperature sintering. The specific heating steps are as follows: First, the temperature was raised from room temperature to 250°C and kept for 60 minutes; Secondly, heat to 500℃ and keep warm for 30min; Then the product is cooled in the furnace to obtain the finished product of the additive granules.

8. The method for preparing porous sodium fluoride adsorbent particles according to claim 1, characterized in that: In the step 1, the auxiliary material mixture is prepared by adding sodium bifluoride aqueous solution to distilled water.

9. The method for preparing porous sodium fluoride adsorbent particles according to claim 1, characterized in that: In the step 1.3, the mass ratio of the main material mixture to the auxiliary material mixture is 1:1.

Citation Information

Cited By

  • Preparation method and application of granular potassium magnesium fluoride adsorbent

    CN120479375A